2020
DOI: 10.1186/s12870-020-02565-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of an anthocyanin-related glutathione S-transferase gene in Japanese gentian with the CRISPR/Cas9 system

Abstract: Background: The blue pigmentation of Japanese gentian flowers is due to a polyacylated anthocyanin, gentiodelphin, and all associated biosynthesis genes and several regulatory genes have been cloned and characterized. However, the final step involving the accumulation of anthocyanins in petal vacuoles remains unclear. We cloned and analyzed the glutathione S-transferases (GSTs) in Japanese gentian that are known to be involved in anthocyanin transport in other plant species. Results: We cloned GST1, which is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Gene editing offers a faster method to develop these crops. New CRISPR-Cas9 (CRISPR for Clustered Regularly Interspaced Short Palindromic Repeats) is a powerful genome editing tool that has recently been widely adopted in model organisms [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene editing offers a faster method to develop these crops. New CRISPR-Cas9 (CRISPR for Clustered Regularly Interspaced Short Palindromic Repeats) is a powerful genome editing tool that has recently been widely adopted in model organisms [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we performed RT-PCR analysis and detected the same sequences corresponding to the edited genomic sequences in each of the three lines. These results clearly showed that the functional knockout of EPH1L was achieved as in the case of the genes involved in flower color [ 21 , 22 ] and overwintering [ 35 ] in gentians.…”
Section: Resultsmentioning
confidence: 92%
“…We used the Japanese cultivated gentian “Albireo” ( Gentiana scabra × Gentiana triflora ) as a WT in this study. The details of this cultivar are described in the manuscript by Tasaki et al [ 22 ]. In this study, WT plants were grown in the fields of the Iwate Agricultural Research Center under natural conditions or in a greenhouse at the Iwate Biotechnology Research Center (IBRC).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations